2005
DOI: 10.14411/eje.2005.095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wolbachia-targeted tetracycline on a host-parasitoid-symbiont interaction

Abstract: Abstract. The uzifly, Exorista sorbillans (Diptera: Tachinidae), a parasite of the silkworm, Bombyx mori L. (Lepidoptera: Bombycidae), causes heavy losses to the silk industry. This parasitoid harbours a Wolbachia endosymbiont, which controls the fly's reproduction. In the present study a method for curtailing this notorious pest by administering Wolbachia-targeted tetracycline via its silkworm host's diet is investigated. Tetracycline not only influenced the larval growth of the silkworms' by decreasing larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Though there are a number of curative measures, the loss of agro-products continues to be 25-30%. Our earlier work showed that some insects and pests of sericulture harbour Wolbachia (Madhu and Puttaraju 2001;Puttaraju and Madhu 2002;Prakash and Puttaraju 2006a) and suggested a novel method for the management of uzifl y, a parasitoid of silkworn (Puttaraju and Prakash 2005a;Puttaraju and Prakash 2005b;Puttaraju and Prakash 2005c;Prakash and Puttaraju 2006b). In the present paper we demonstrate the frequency of double versus single infection of Wolbachia using ftsZ A-and B-specifi c primers (Prakash 2006) in some insects and pests associated with mulberry and silkworn.…”
Section: Frequency Of Infection With a And B Supergroupmentioning
confidence: 99%
“…Though there are a number of curative measures, the loss of agro-products continues to be 25-30%. Our earlier work showed that some insects and pests of sericulture harbour Wolbachia (Madhu and Puttaraju 2001;Puttaraju and Madhu 2002;Prakash and Puttaraju 2006a) and suggested a novel method for the management of uzifl y, a parasitoid of silkworn (Puttaraju and Prakash 2005a;Puttaraju and Prakash 2005b;Puttaraju and Prakash 2005c;Prakash and Puttaraju 2006b). In the present paper we demonstrate the frequency of double versus single infection of Wolbachia using ftsZ A-and B-specifi c primers (Prakash 2006) in some insects and pests associated with mulberry and silkworn.…”
Section: Frequency Of Infection With a And B Supergroupmentioning
confidence: 99%
“…Exorista sorbillans is a larval endoparasitoid of silkworm Bombyx mori (Jolly 1981; Srikanth et al. 1991), which harbors Wolbachia (Madhu & Puttaraju 2001; Puttaraju & Madhu 2002; Puttaraju & Prakash 2005a,b,c; Prakash & Puttaraju 2006a). The female uzifly lays an average of 500 eggs (Puttaraju & Prakash 2005a) on the body of third to fifth instar silkworm larvae, within which parasitic maggots subsequently feed and develop.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was carried out with a PTC 200 Thermalcycler (MJ Research, Walthman, USA). The thermal conditions were followed as described elsewhere (Puttaraju & Prakash 2005a,c). The amplified PCR products were separated through 1.3% agarose gel electrophoresis run in 1 × TBE (89.2 mM Tris‐HCl, 88.9 mM boric acid, 2.0 mM disodium‐ethylenediaminetetra‐acetic acid) buffer for a length of 5–6 cm at a constant of 65 V from a power supply unit, (EP S200V/400 mA, Amersham Pharmacia Biotech, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations